2002
DOI: 10.1016/s0893-133x(01)00299-8
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine and Amphetamine Depress Striatal GABAergic Synaptic Transmission through D2 Dopamine Receptors

Abstract: The striatum is a brain area implicated in the pharmacological action of drugs of abuse. To test the possible involvement of both cocaine and amphetamine in the modulation of synaptic transmission in this nucleus, we coupled whole-cell patch clamp recordings from striatal spiny neurons to the focal stimulation of glutamatergic or GABAergic nerve terminals. We found that neither cocaine (1-600 M) nor amphetamine (0.3-300 M) significantly affected the glutamate-mediated EPSCs recorded from these cells. Conversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 75 publications
(85 reference statements)
4
56
0
Order By: Relevance
“…In agreement with other studies demonstrating that acute cocaine application in corticostriatal slices affects synaptic transmission through D2 receptors (Centonze et al, 2002;Wu et al, 2007;Tozzi et al, 2012), we found that the effect of cocaine on synaptic transmission is prevented by D2 receptor blockade.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other studies demonstrating that acute cocaine application in corticostriatal slices affects synaptic transmission through D2 receptors (Centonze et al, 2002;Wu et al, 2007;Tozzi et al, 2012), we found that the effect of cocaine on synaptic transmission is prevented by D2 receptor blockade.…”
Section: Discussionsupporting
confidence: 93%
“…Striatal D 2 receptor stimulation results in a decreased release of GABA (Girault et al, 1986;Centonze et al, 2002), leading to speculation that D 2 receptor antagonism via medication could result in increased GABA release, as observed in the current preliminary analysis. Indeed, antipsychotic treatment in rats induces elevation of GABAergic activity and release in the striatum (Osborne et al, 1994).…”
Section: Treatment Statusmentioning
confidence: 50%
“…In the present study, we found that systemic or intra-NAc GVG dose-dependently elevated extracellular GABA, which lasted for at least 5-6 h. Given that GVG did not inhibit cocaine-induced increases in NAc DA, we believe that GVG-induced increases in GABA may play a more direct role in inhibiting cocainetriggered reinstatement than we had previously surmised. It is well documented that GABAergic neurons in the brain's reward circuitry play an important role in opiate or psychostimulant reward (Koob and Bloom, 1988;Self and Nestler, 1995;Wise, 1998;Xi and Stein, 2002), and that cocaine, opiates and DA produce an inhibitory effect on GABAergic neurons or GABA release in their projection areas (Uchimura and North, 1990;Qiao et al, 1990;White et al, 1993;Cameron and Williams, 1994;Nicola and Malenka, 1997;Xi and Stein, 2002;Centonze et al, 2002). Based on this, we believe that GVG-elevated GABA levels in brain reward circuitry might directly counteract the actions of cocaine, opiates or DA on GABAergic neurons, thereby antagonizing cocaine-induced reinstatement of drug-seeking behavior.…”
Section: Gabaergic Mediation Of Gvg's Inhibition Of Drug-seeking Behamentioning
confidence: 99%